Zonation and Associations of Dominant Fish Fauna in Flemish Cap - Paz, Xabier; Casas-Sánchez, José Miguel (1995)
Data from 682 demersal traws between 126 and 738 m were made on Flemish Cap in summer during the research surveys in the years 1989-1994. Despite the fact that the depth range for all species was not completely covered, analysis of the vertical distribution of the 25 most representative species showed that the fauna is zoned with depth. Distinct faunal assemblages with characteristic catch rates, diversity, and dominant species are found on the shelf (126-300 m), upper continental slope (300-600 m) and middle continental slope (> 600 m). Catch rates are greatest on the shelf and upper continental slope, as while as diversity is greatest on the middle continental slope. Dominance of the commercial species (Cod, Redfish, American plaice, Greenland halibut) is an important aspect of the community structure. Diversity patterns may be understood in terms of the relationships with predation, competition, environmental heterogeneity, and trophic level. Also the influence of the fisheries in the area can modify this structure. Only Synaphobranchus kaupy, Sebastes marinus and Reinhardtius hippoglossoides showed a significant bigger-deeper relation, while Anarhichas minor and Glyptocephalus cynoglossus has a smaller-deeper relation.